Free Inbound Student Exchange Batch 2 at Jambi University by University Students August 17, 1945 Surabaya - Arlista Dewi Januariska (PT FORMOSA CENDEKIA GLOBAL, 2022)
The policy of Mr. Nadiem Makarim as the Minister of Education and Culture is the Freedom to Learn the Independent Campus policy There are 9 types of programs at the University of 17 August 1945 Surabaya, one of which is the Free Student Exchange This study aims to describe the activities carried out during the Batch 2 Independent Student Exchange Program at the University of Jambi and the conversion courses from PT senders. The research method used is qualitative method. The subjects of this study were 119 inbound students and students from the University of 17 August 1945 Surabaya. Data collection was carried out using observation and documentation techniques. With the activities of the Independent Student Exchange The program is very useful for students in improving soft skills and hard skills, broaden academic knowledge, increase friendship relations from various tribes, cultures, religions, races that stretch from Sabang to Merauke